Copper or/and arsenic induce oxidative stress-cascaded, nuclear factor kappa B-dependent inflammation and immune imbalance, trigging heat shock response in the kidney of chicken - Wang, Yu (Oncotarget, 2017)
Excessive amount of copper (Cu) and inorganic arsenic (iAs) coexists in drinking water in many regions, this is associated with high risk of nephropathy, defined as chronic structural and functional disorders of the kidney. However, the underlying mechanisms are not well understood. In this study, a total of 72 day-old Hy-line chickens were exposed to 300 mg/kg copper sulphate or/and 30 mg/kg arsenic trioxide for 12 weeks. Indicators of oxidative stress, inflammation and heat shock proteins (HSPs) production were analyzed in kidney. The results showed that, when the toxicant was administrated alone, there is an antagonism between redox homeostasis during the first 4 weeks, which follows a collapse of antioxidant system manifested by damaged biomembrane structure. What's worse, oxidative damage-cascaded histopathological lesions were accompanied by increases of proinflammatory mediators and an imbalance of “Th1/Th2 drift” (Th, helper T cell) regulated by nuclear factor kappa B (NF-κB). Simultaneously, intense heat shock response went with the organism. The above-mentioned renal lesions and indicators changes were time-dependent, more complex and deteriorated effects were observed in Cu/iAs combined groups compared with the others. This study supports Cu and iAs have a synergistic type on the nephro-toxicological process additively. In conclusion, oxidative stress and inflammatory induced by Cu or/and iAs are potential mechanisms in their nephrotoxicity, increased heat shock response may play a renoprotection function in tissues damage.